THERAPY OF ENDOCRINE DISEASE: Testosterone supplementation and body composition: results from a meta-analysis study. Issue 3 (March 2016) - Corona, Giovanni; Giagulli, Vito A; Maseroli, Elisa; Vignozzi, Linda; Aversa, Antonio; Zitzmann, Michael; Saad, Farid; Mannucci, Edoardo; Maggi, Mario
Abstract : Objective: The role of testosterone (T) in regulating body composition is conflicting. Thus, our goal is to meta-analyse the effects of T supplementation (TS) on body composition and metabolic outcomes. Methods: All randomized controlled trials (RCTs) comparing the effect of TS on different endpoints were considered. Results: Overall, 59 trials were included in the study enrolling 3029 and 2049 patients in TS and control groups respectively. TS was associated with any significant modification in body weight, waist circumference and BMI. Conversely, TS was associated with a significant reduction in fat and with an increase in lean mass as well as with a reduction of fasting glycaemia and insulin resistance. The effect on fasting glycaemia was even higher in younger individuals and in those with metabolic diseases. When only RCTs enrolling hypogonadal (total T <12 mol/l) subjects were considered, a reduction of total cholesterol as well as triglyceride (TGs) levels were also detected. Conversely, an improvement in HDL cholesterol levels as well as in both systolic and diastolic blood pressure was not observed. Conclusion: Our data suggest that TS is able to improve body composition and glycometabolic profile particularly in younger subjects and in those with metabolic disturbances. Specifically designed studies are urgently needed to confirm this point.